Investigations of plasma wake-fields in NSC KIPT - Onishchenko, I.N. (Вопросы атомной науки и техники, 2000)
Along with reviewing of the world wide investigations of wakefields, excited in plasma by a short electron bunch or a train of bunches and by laser beat-wave or a short laser pulse, the theoretical and experimental research activity in National Science Center “Kharkov Institute of Physics and Technology” (NSC KIPT) with the aim of plasma wakefields excitation by a train of relativistic electron bunches, produced by resonant lin acs, are represented. The considerable attention is devoted to the wakefields investigation in the experimental department, headed by A.K.Berezin. Plasma wakefields are reviewed as a tool for elaboration of accelerators of new generation, plasma lens for relativistic electron beam focusing, and for development of new principles of HF-generators construction The researching works performed in NSC KIPT and planned in the future are discussed. The state of art and perspectives of theoretical and experimental investigations are considered. The recent achievements in the laboratories of the world are represented.